Diary record survey (Melaka UNESCO World Heritage Site) - Ab Rahman, Syakir Amir (2020)
The diary record survey is one of the quantitative data collection methods in research process. The record survey was used to collect and record the domestic and inbound tourists' expenditure in Melaka UNESCO World Heritage Site. The record survey covers several tourism sectors namely, accommodation, food and beverage, transportation, shopping and entertainment.